Management Strategy of the Amil Zakat Institution (LAZ) Persada Bojonegoro in Improving the Welfare of Orphans and the Poor - Syaifudin, Ahmat Arif; Hualika, Mifta; Reza, Silvania Asmara (GERASI INSAN NUSANTARA, 2025)
Zakat is an obligation for capable Muslims and is intended for those who are entitled to receive it. Zakat funds have great potential to improve the overall welfare of society. This study aims to examine the management strategies of the Amil Zakat Institution (LAZ) Persada Jatim Indonesia in enhancing the welfare of orphans and the poor in Bojonegoro, as well as to identify its supporting programs. This research employs a descriptive qualitative method using field interviews, observation, and documentation as data collection techniques. The results show that LAZ Persada Jatim Indonesia implements three strategies to increase community participation in improving the welfare of orphans and the poor: personal fundraising (relying on the ability of individual fundraisers), corporate fundraising (targeting companies with CSR funds), and digital fundraising (utilizing social media). In addition, there are twelve supporting programs conducted by LAZ Persada Jatim Bojonegoro to promote the welfare of orphans and the poor in the region